The martial artist's book of five rings the definitive interpretation of Miyamoto Musashi's classic book of strategy - Kaufman, Steve 1939- (CE Turtle, 1994)
Miyamoto Musashi's The Book of Five Rings is well known book of strategy and has been used to understand contemporary Japanese business. However, Musashi was not a business person but a martial artist, a swordsman--the greatest warrior Japan has ever known--and his Five Rings was his definitive treatise on mortal combat. Kaufman, the "Founding Father of American Karate" has 40 years of experience and holds the highest rank attainable in the martial arts. His interpretation of Musashi's classic is specifically for the martial artist as it was originally intended. The result is an enthralling treatise on martial strategy that combines a warrior's instinct with the philosophies of Buddhism, Shintoism, Confucianism, and Taoism.